Click to Protect: Digital Activism Journey of Handling and Prevention of Sexual Violence Task Force in Indonesia - Uzdah Wulandari, Putri; Juwita Sari, Etsa; Rahayu, Esti (Indonesian Association for Public Administration (IAPA), 2024)
This research aims to analyze the digital activism carried out by the Task Force for the Prevention and Handling of Sexual Violence (PPKS Task Force) in addressing the issue of sexual violence in higher education institutions in Indonesia. This study focuses on the preventive and promotive actions implemented through the social media platform Instagram by the PPKS Task Force. This research utilizes a quantitative-based comparative content analysis, and it examines 2,795 posts from 46 universities in Indonesia. The findings highlight several categories of published content, such as information, outreach, collaboration, celebrations, events, and others aimed at raising awareness and public participation in the issue of sexual violence. Furthermore, the study identifies variations in digital interaction patterns between PPKS Task Force and its audience. It indicates significant differences in how messages are conveyed and their impact on Instagram users, particularly the academic community at these universities. This study provides valuable insights into how PPKS Task Force's digital activism can influence the public in efforts to prevent sexual violence in higher education institutions. Additionally, it contributes to the literature on digital activism in Indonesia, particularly concerning sensitive issues like sexual violence.